ANALISIS TINGKAT KEBANGKRUTAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (Studi pada Perusahaan yang Terdaftar d Bursa Efek Indonesia 2013-2015) - Diah Isti Ridha Buari; Istiatin Istiatin; Djumali Djumali (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
The purpose of this research study is to determine the result of prediction analysis of potential bankruptcy on four manufacturing companies in food and beverage sector which has been listed in Indonesia Stock Exchange year 2013 to 2015. Type of research used in this study is descriptive research with quantitative approach. This study uses secondary data such as financial statements of company with data collection documentation and library research. Based on the results and conclusions of the analysis using Altman Z-Score method showed that: (1) PT Mayora Indah Tbk in 2013 and 2014 were in vulnerable bankruptcy (grey), but in 2015 PT Mayora Indah Tbk could improve its financial performance so as tp be in healthy category. (2) PT Indofood Sukses Makmur in 2013 to 2015 are in vulnerable bankruptcy (grey). (3) PT Wilmar Cahaya Indonesia Tbk in 2013 to 2015 are in healthy category (not insolvent). (4) PT. Ultra Jaya Milk Industry and Trading Company Tbk in 2013 to 2015 are in healthy condition. Keywords : Manufacturing companies in food and beverage sector, Bankruptcy, Altman Z-Score